Antigen dose, type of antigen-presenting cell and time of differentiation contribute to the T helper 1/T helper 2 polarization of naive T cells - Rothoeft, T (Blackwell Science Inc, 2003)
Antigenic encounter by T cells induces immunological synapse formation and T-cell activation. Using different concentrations of toxic shock syndrome toxin-1 (TSST-1) as stimulus, we examined the capacities of dendritic cells (DC) and macrophages (Mφ) to prime syngeneic naive T cells. DCs were, under all experimental settings, more efficient than Mφ at clustering T cells. Translocation of the T-cell receptor (TCR) to the contact area was found to be induced by DCs, as well as by Mφ, in an antigen-dependent manner, although Mφ were less efficient at inducing TCR translocation. Capping of protein kinase C θ (PKCθ) was also antigen dependent but induced exclusively by DCs. Likewise, DCs were found to be more potent inducers of interleukin-2 (IL-2) production and proliferation of naive T cells than Mφ. After 3 days of culture, DCs presenting 100 ng/ml TSST-1 induced interferon-γ (IFN-γ)-secreting cells, whereas Mφ did not. After 7 days of culture, DCs presenting 0·1 ng/ml TSST-1, and Mφ presenting high (as well as low) doses of TSST-1, induced IL-4-producing cells. We therefore provide evidence to show that antigen dose, type of antigen-presenting cell and time of differentiation can contribute to T-cell differentiation.